2015
DOI: 10.3332/ecancer.2015.525
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin modulates cellular AP-1, NF-kB, and HPV16 E6 proteins in oral cancer

Abstract: In this study, we investigated the effects of the natural antioxidant curcumin on the HPV16-positive oral carcinoma cell line 93VU147T and demonstrated that curcumin is not only a potent inhibitor for the activity of host nuclear transcription factors AP-1 and NF-kB but it also selectively suppresses transcription of the HPV16/E6 oncogene during the carcinogenic process in oral cancer cells. This study suggests a therapeutic potential of curcumin for high-risk human papilloma virus (HPV)-infected oral cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 33 publications
3
58
0
Order By: Relevance
“…However, NF-kB affords tumor cell protection by inducing Bcl-2 expression, whereas p53 promotes apoptosis by boosting the expression of the pro-apoptotic protein Bax [ 21 ]. Curcumin causes inactivation of the transcription factors AP-1 and NF-kB, which have been implicated in the transcription of HPV-associated proteins such as E6 and E7 [ 22 ]. This curcumin-evoked inhibition of NF-kB and the consequent suppression of E6 [ 21 ], leads to induction of p53, suppression of the NF-kB-Bcl-2 protective pathway, and preferential stimulation of the p53-Bax apoptotic pathway in cancer cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, NF-kB affords tumor cell protection by inducing Bcl-2 expression, whereas p53 promotes apoptosis by boosting the expression of the pro-apoptotic protein Bax [ 21 ]. Curcumin causes inactivation of the transcription factors AP-1 and NF-kB, which have been implicated in the transcription of HPV-associated proteins such as E6 and E7 [ 22 ]. This curcumin-evoked inhibition of NF-kB and the consequent suppression of E6 [ 21 ], leads to induction of p53, suppression of the NF-kB-Bcl-2 protective pathway, and preferential stimulation of the p53-Bax apoptotic pathway in cancer cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, a pharmacologically safe herbal compound is known for its anticancer effects, including inhibition of proliferation and angiogenesis, induction of apoptosis and increased chemo-radiosensitivity ( 8 11 ).Recent studies have demonstrated curcumin as a potent inhibitor of AP-1, NF-kB, and HPV in cervical and oral cancer ( 11 15 ) but its effects on oral cancer and CSCs with or without HPV infection are unknown. Therefore, the present study was performed to clarify the effects of curcumin in OSCC-CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…As a natural compound, it has been proven to be effective with minimal toxicity, which selectively acts on cancer cells over normal cells (5,6). Hitherto, curcumin and its analog have been reported to play an anticancer role in several tumor models, including glioblastoma (7), liver (8), colorectal (9), lung (10), ovarian (11), breast (12) and oral (13) cancer. The underlying mechanisms have been demonstrated to be associated with the inhibition of proliferation, angiogenesis, invasion and metastasis of cancer cells, or apoptosis induction by curcumin (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%